Studies in Symbolic Interaction - Denzin, Norman K. (Studies in Symbolic Interaction Ser., 2021)
Volume 53 of Studies in Symbolic Interactionis divided into three parts, providing contemporary readings of social situations, including interpreting translational science, an analysis of the 'Phantasmal in Qualitative Research' and 'Miami's Sea-level Rise Committee'.